Comparison of the removal ability of basket catheters for small bile duct stones impacted in the corner pocket of the lower bile duct - Inoue, Tadahisa; Ibusuki, Mayu; Kitano, Rena; Sakamoto, Kazumasa; Kimoto, Satoshi; Kobayashi, Yuji; Sumida, Yoshio; Nakade, Yukiomi; Ito, Kiyoaki; Yoneda, Masashi (Endoscopy, 2022)
Background Endoscopic stone extraction is often challenging in patients with a significant lower bile duct corner pocket, where small stones are likely to escape and become impacted. This study aimed to determine the utility of different types of baskets for retrieving corner pocket stones.Methods Seven types of retrieval baskets were evaluated on silicone models. The study outcomes included the characteristics of each basket and technical success rates associated with the retrieval of stones impacted in the corner pocket.Results The overall success rate was only 27.5 %, with significant differences between the baskets (P < 0.001). Only three baskets yielded successful removal. The success rates were 10 %, 25 %, and 70 % with the 8-wire Nitinol Basket, RASEN, and VorticCatch V, respectively, all of which are helical eight-wire baskets. RASEN and VorticCatch V share similar characteristics, including a strong spiral wire and smaller interwire spaces at their distal ends. The addition of rotation significantly increased the success rate to 80 % with the 8-wire Nitinol Basket (P < 0.001) and 90 % with RASEN (P < 0.001).Conclusions Robust helical eight-wire baskets with smaller interwire spaces at the tip may be effective for extracting corner pocket stones, while the addition of rotational motion may improve the efficacy of retrieval.